2006
DOI: 10.1139/x05-309
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in basal area increment phenology and its correlation with growth rate in loblolly and slash pine families and clones

Abstract: We quantified basal area increment phenology over a 2-year period in one loblolly pine (Pinus taeda L.) and four slash pine (Pinus elliottii Engelm. var. elliottii) full-sib families propagated as rooting cuttings. In 2002, basal area growth started in March and stopped in October for both species, while in 2003, initiation and cessation occurred 2 weeks earlier for all families. In both years, peaks in basal area increment occurred in short (2–3 week) periods in the early spring for all families, followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…For several Larix species, BALTUNIS and GREENWOOD (1999) found that total height was positively correlated with the date of cessation of shoot growth and the total duration of growth but not with the time of shoot initiation and with the rate of elongation. In some other studies (MCCRADY and JOKELA, 1996;EMHART et al, 2006), no significant differences could be found for these growth phenology parameters among families or even among species probably due to a more restricted origin of their genetic material.…”
Section: Contribution Of Growth Phenology and Growth Rhythm Parametermentioning
confidence: 76%
See 1 more Smart Citation
“…For several Larix species, BALTUNIS and GREENWOOD (1999) found that total height was positively correlated with the date of cessation of shoot growth and the total duration of growth but not with the time of shoot initiation and with the rate of elongation. In some other studies (MCCRADY and JOKELA, 1996;EMHART et al, 2006), no significant differences could be found for these growth phenology parameters among families or even among species probably due to a more restricted origin of their genetic material.…”
Section: Contribution Of Growth Phenology and Growth Rhythm Parametermentioning
confidence: 76%
“…hybrids and their related parents in this study) and thus ways by which heterosis is built up over the growing season. Indeed as shown by EMHART et al (2006), the significant differences observed in basal area size among two pine species (Pinus taeda and P. elliottii) were explained by differential growth rates expressed only during short, discrete time periods. In fact, a more detailed look on growth rhythms in our study (such as plotted in Figure 2) revealed contrasting situations for expression of hybrid vigour over the growing season.…”
Section: Contribution Of Growth Phenology and Growth Rhythm Parametermentioning
confidence: 91%
“…The date of initiation and cessation determine the duration of growth, and those factors together with the daily rate of growth determine the total growth for the season (Emhart et al 2006). BC1 started growth earlier than was estimated from the initial measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Initiation differed by more than 20 days, whereas cessation only differed by 8 days. These differences could have been caused by siteto-site variation (Parisi 2006) or year-to-year variation (Jayawickrama et al 1998;Emhart et al 2006). BC1 demonstrated positive and negative heterosis for several traits and no heterosis for others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation